2014
DOI: 10.5398/medpet.2014.37.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Digestibility and Performances of Frisian Holstein Calves Fed with Pennisetum purpureum and Inoculated with Buffalo’s Rumen Bacteria

Abstract: Buffalo's rumen bacteria (BRB) are potential in digesting fiber feed. BRB already adapted well with low quality forages and agricultural byproducts. The aim of this study was to determine the effect of buffalo's rumen bacteria (BRB) consortium inoculated into preweaning Frisian Holstein calves on nutrient digestibility, physiological status, mineral uptake, and blood profile. This study used 14 isolates of bacteria isolated from rumen fluid of four local buffalos. The research units consisted of seven Frisian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The cellulolytic R. albus KU-F152 and non-cellulolytic S. ruminantium S137 supplementation had no negative effects on the feed intake, final weight, weight gain and ADG of Holstein steers. Prihantoro et al [26] reported that the inoculation of ruminal bacterium increased the feed intake and ADG (19.47%) of Holstein calves during the weaning period. In the current study, R. albus and S. ruminantium inoculation increased the final weight, weight gain and ADG compared to the non-inoculated control by 4.46%, 16.45% and 16.13%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellulolytic R. albus KU-F152 and non-cellulolytic S. ruminantium S137 supplementation had no negative effects on the feed intake, final weight, weight gain and ADG of Holstein steers. Prihantoro et al [26] reported that the inoculation of ruminal bacterium increased the feed intake and ADG (19.47%) of Holstein calves during the weaning period. In the current study, R. albus and S. ruminantium inoculation increased the final weight, weight gain and ADG compared to the non-inoculated control by 4.46%, 16.45% and 16.13%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These results were due to R. albus KU-F152 and S. ruminantium S137 increasing the feed digestion efficiency [5,27]. Similarly, Prihantoro et al [26] reported that buffalo rumen bacteria resulted in a relative improvement in the feed digestive efficiency of Holstein calves during the weaning period. In the current study, R. albus KU-F152 and S. ruminantium S137 increased the total VFA content in the rumen fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation